A Simple Data Mining Model for Heart Disease Prediction - Santhosh Kumar Sundar (Journal of Global Pharma Technology, 2018)
The large amounts of data require information retrieval techniques to extract useful information. Medical data is generally complex and in large volumes.  Data mining techniques are widely used in medical field for various purposes. One of the important applications in medical data analysis is the prediction of diseases. Non Communicable Diseases (NCD) is known as life style disease which requires the medical history of patient. Among other diseases in NCD, Heart disease is the leading cause of death in the world. Heart disease affects the normal functionality of heart. The health care industry gives the huge amount of the health care data and that need to be mined to ascertain hidden information. With the help of data mining and medical history, the early prediction of heart disease can be possible. This paper focuses about the early prediction of heart disease using data mining techniques. For that classification and clustering algorithms are used.Keywords: Non Communicable Disease, Heart Disease, Medical Data Mining, Clustering, Classification.